Nuciferine Inhibited the Differentiation and Lipid Accumulation of 3T3-L1 Preadipocytes by Regulating the Expression of Lipogenic Genes and Adipokines - Xu, Hanyuan; Wang, Linjie; Yan, Kemin; Zhu, Huijuan; Pan, Hui; Yang, Hongbo; Liu, Meijuan; Gong, Fengying (Frontiers in Pharmacology, 2021)
Purposes: Nuciferine, a main aporphine alkaloid component found in lotus leaf (Nelumbo nucifera), has been demonstrated to possess the property of reducing fat mass and alleviating dyslipidemia in vivo. The purpose of this study is to explore the effects of nuciferine on the proliferation and differentiation of 3T3-L1 cells and further investigate the possible mechanisms. Methods: 3T3-L1 preadipocytes were treated with 0~20 μM nuciferine for 24~120 h, the cell viability was assessed using CCK8. 3T3-L1 preadipocytes and human primary preadipocytes were then induced differentiation and the effects of nuciferine on lipid metabolism in differentiating and fully differentiated adipocytes were observed by the methods of intracellular triglyceride (TG) assay, Oil Red O staining, RT-qPCR and western blot. Transient transfection and dual luciferase reporter gene methods were used to assess the effects of nuciferine on FAS promoter activities. Results: Nuciferine inhibited the proliferation of 3T3-L1 preadipocytes in a dose- and time-dependent manner. 20 μM nuciferine significantly attenuated lipid accumulation and reduced intracellular TG contents by 47.2%, 59.9% and 55.4% on the 3rd, 6th and 9th day of preadipocytes differentiation, respectively (all P<0.05). Moreover, the mRNA levels of PPARγ, C/EBPα, C/EBPβ, FAS, ACC, HSL and ATGL were notably decreased by 39.2~92.5% in differentiating preadipocytes (all P<0.05). In fully differentiated adipocytes, the mRNA levels of FAS, ACC and SREBP1 were remarkably downregulated by 22.6~45.2% compared with the controls (0 μM) (all P<0.05), whereas the expression of adipokines FGF21 and ZAG were notably promoted by nuciferine. Similar results were obtained in fully differentiated human primary adipocytes treated with nuciferine (all P<0.05). Further mechanism studies showed that 2.5~20 μM nuciferine significantly decreased FAS promoter activities in 3T3-L1 preadipocytes. Conclusions: Nuciferine inhibited the proliferation and differentiation of 3T3-L1 preadipocytes. The inhibitory effects of nuciferine on adipogenesis might be due to the downregulation of PPARγ, C/EBPα and C/EBPβ, which led to the reduction of intracellular lipid accumulation in 3T3-L1 cells and by downregulating the expression of critical lipogenic enzymes, especially of FAS, which was achieved by inhibiting the FAS promoter activities. Besides, nuciferine promoted the expression of adipokines in fully differentiated adipocytes.